Analisis Dan Perancangan Sistem Informasi Administrasi Keuangan Siswa Pada SMK PGRI 2 Kota Jambi - Sari, Ika Novita; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
Financial administration of students at SMK PGRI 2 Jambi in paying school tuition (SPP) still manual so that every students who will pay have to stand in line for a long time. The purpose of this study to analyze and design information system of students’ financial administration at SMK PGRI 2 Kota Jambi. The method that is used in this analysis and design is Data Flow Diagram. This study has created a prototype of information system of students’ financial administration. I hope this prototype Information System of Students’ Financial Administration can be implemented at SMK PGRI 2 Kota Jambi.